Parent-of-origin testing of prenatal copy number variations: a retrospective study of 167 family cases - Yuefang Liu; Yuan Peng; Zhe Liang; Qiong Pan (Scientific Reports)
Abstract Low-penetrance pathogenic copy number variations (CNVs), variation of uncertain significance (VUS) CNVs and likely pathogenic CNVs present a challenge for prenatal diagnosis. Previous studies have clarified the influence of a parent-of-origin test on the prenatal VUS CNVs. However, the influence of parent-of-origin tests on prenatal likely pathogenic (LP) or low-penetrance pathogenic CNVs (pCNVs) have not been evaluated. Here, among 2273 pregnant women undergoing prenatal diagnosis, 236 CNVs were reported by chromosomal microarray analysis (CMA) including 69 full-penetrance pCNVs, 44 low-penetrance pCNVs, 113 VUS CNVs and 10 LP CNVs. Based on the subsequent parent-of-origin tests, CNVs were classified as de novo, inherited and unknown group. Firstly, a total of 112 couple (62 VUS CNVs, two LP CNVs and 48 pCNVs) chose parent-of-origin tests and 88 inherited CNVs (51 VUS CNVs, two LP CNVs and 35 pCNVs ) were identified. Then, the effect of parent-of-origin tests was focused on 44 low-penetrance pCNVs, 113 VUS CNVs and 10 LP CNVs in this study (n = 167). For 44 low-penetrance pCNVs, termination of pregnancy (TOP) rates in de novo, inherited and unknown group were 100% (5/5), 23.5% (4/17) and 40.9% (9/22), respectively. TOP decisions in low-penetrance pCNVs were mainly affected by de novo and abnormal ultrasound findings. For 113 VUS CNVs, inherited VUS CNVs dramatically reduced anxiety reflected by TOP rates in de novo (18.2%, 2/11), inherited (0/51) and unknown group (2.0%, 1/51). Notably, prenatal minor structural defects often disappeared after birth. These results suggested the majority VUS CNVs have no appreciable pathogenicity. For 10 LP CNVs, TOP rates in inherited and unknown group were 0% (0/2) and 87.5% (7/8), which suggested that it is imperative that parent-of-origin tests be offered for LP CNVs to bring the classification to pathogenic or VUS.